Increase product sales of electronic companies by using IT applications in creating an effective e-marketing plan in social virtual worlds - Read, Mohamed Nazir; Zailan Arabee, (2011)
The objective of this research is to determine the effect of using IT applications for e-marketing in social virtual worlds on real products sales by focusing on electronic companies. The findings of this research suggests that marketers have to use specialized IT applications for e-marketing in social virtual worlds, which can improve the interaction with virtual products, and this can lead to an increase in the real product sales.